PEMANFAATAN MEDIA DIGITAL UNTUK MENINGKATKAN MINAT BELAJAR SISWA SD NEGERI 140 PALEMBANG - Iis Amalia; Meylinda Aulia Mulyaningsih; Anggri Setiawan; Reva Zalianti; Dian Maya Sari; Yopi Intan Permata; Devi Septiana; Rizki Kurniawansyah; Mega Prasrihamni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the use of digital media in increasing student learning interest at SD Negeri 140 Palembang. The development of digital technology provides opportunities for teachers to create interesting, interactive learning that is in accordance with the characteristics of students in elementary schools. The study used a qualitative descriptive approach, namely data collection techniques in the form of observation, interviews, and documentation. The results of this study indicate that the use of digital media such as learning videos, presentations, interactive, educational applications and internet-based learning platforms can increase student attention, motivation and participation in the learning process. The use of digital media also helps teachers deliver material effectively and easily understood by students. Digital media has a positive impact on increasing student learning interest at SD Negeri 140 Palembang.